Bronchoscopy, Ultrasound, and Video Laryngoscopy as Guidelines for Percutaneous Dilatation Tracheostomy (PDT) in Patients with Difficult Airway Suspected of Laryngeal Tumor - Sutan Syarif Muda Dalimunthe; Edi Daramawan; Rizki Taufiqurrahman; Bastian Lubis; Andriamuri Primaputra Lubis; Rommy Fransiscus Nadeak; Dis Bima Purwaamidjaja; Ferdinand Chandra (Journal of Society Medicine, 2026)
Introduction: Percutaneous dilatational tracheostomy (PDT) is the preferred technique for elective tracheostomy in critically ill patients. However, a laryngeal or cervical mass is a relative contraindication because landmark puncture is unreliable, bleeding risk increases, and the airway may be lost when the endotracheal tube is withdrawn. Evidence on the safe extension of PDT to such airways is limited. Case Description: A 72-year-old man was admitted to H. Adam Malik General Hospital, Medan, Indonesia, with decreased consciousness after being struck by a motorcycle. Tracheal intubation was unexpectedly difficult and required a video laryngoscope and bougie. After eight days of ventilation, weaning failed, and tracheostomy was indicated. Pre-procedural neck ultrasound showed peritracheal soft-tissue thickening suspicious for a laryngeal tumor without compression of the tracheal lumen and identified a puncture interspace free of large vessels. Open tracheostomy was initially considered because of anticipated bleeding; however, bedside PDT was performed under triple guidance: ultrasound for site selection, video laryngoscopy to inspect the larynx and confirm endotracheal tube position, and flexible bronchoscopy through the tube for continuous intraluminal vision during needle puncture, guidewire passage, dilatation with the Ciaglia Blue Rhino system, and cannula insertion. The correct position was confirmed bronchoscopically before fixation. Conclusion: Combined ultrasound, video laryngoscopic, and bronchoscopic guidance eliminated every blind step and converted a tracheostomy that would conventionally have been performed openly into a controlled bedside intervention. This strategy may be considered an adjunct to standard PDT in selected high-risk patients provided adequate equipment and at least two trained operators are available.